Incarcerated Foreign Minors in Italy: How to Treat them? - Grattagliano, Ignazio; Lisi, Andrea; Massaro, Ylenia; Stallone, Valentina; Campobasso, Filippo; Cannito, Anna; Signorile, Christian; Petruzzelli, Nicola; Catanesi, Roberto (International Journal of Criminology and Sociology, 2013)
The aim of this study is to provide data regarding the treatment of foreign juveniles in the Italian justice system. The authors examined the records from juvenile detention centers and primary juvenile reception centers in Italy in order to gain a better understanding of how foreign minors are treated with respect to their Italian counterparts. Statistical analysis was then carried out and the results revealed many inequalities. The authors believe that it is important to create secondary and tertiary prevention services in order to decrease the likelihood of recidivism, and to promote the minor’s integration into the social fabric of their adopted country. Foreign minors are more frequently placed in jail than their Italian counterparts. The authors conclude that only through the development of a united partnership can a welcoming network be created: one that is able to pick up on the first signs of trouble that often confront foreign minors.